2020
DOI: 10.3390/pharmaceutics12100983
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Biopolymeric Electrospun Nanofibers Based on Polysaccharides for Wound Healing Management

Abstract: Currently, despite the thoroughgoing scientific research carried out in the area of wound healing management, the treatment of skin injuries, regardless of etiology remains a big provocation for health care professionals. An optimal wound dressing should be nontoxic, non-adherent, non-allergenic, should also maintain a humid medium at the wound interfacing, and be easily removed without trauma. For the development of functional and bioactive dressings, they must meet different conditions such as: The ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(73 citation statements)
references
References 192 publications
(236 reference statements)
0
72
0
1
Order By: Relevance
“…Electrospun technology has been widely applied in skin tissue engineering because of several fundamental features beneficial for rapid and functional wound healing and regeneration ( Aavani et al, 2019 ). The biomimetic ECM nanofibrous architecture provides a platform for suitable cell–material interactions and material structure based intracellular signaling pathway activation ( Iacob et al, 2020 ). In addition, the nanopores within the electrospun membranes can increase the nutrient and waste exchange, and form a physical barrier to resist bacterial infection.…”
Section: Resultsmentioning
confidence: 99%
“…Electrospun technology has been widely applied in skin tissue engineering because of several fundamental features beneficial for rapid and functional wound healing and regeneration ( Aavani et al, 2019 ). The biomimetic ECM nanofibrous architecture provides a platform for suitable cell–material interactions and material structure based intracellular signaling pathway activation ( Iacob et al, 2020 ). In addition, the nanopores within the electrospun membranes can increase the nutrient and waste exchange, and form a physical barrier to resist bacterial infection.…”
Section: Resultsmentioning
confidence: 99%
“…It was indicated that electrospun plants and their derivatives' nanofibers such as polysaccharides provide unique characteristics which will lead to enhancing wound healing, such as good biocompatibility, liquid absorption, strong durability, minimum toxicity, and antibacterial activities. Lacob et al [15]. The impact of the aligned and randomly orientated PCL scaffolds was studied by Abbasi et al [16] on quantitative gene expression during neural stem cell differentiation by real-time polymerase chain reaction (RT-PCR).…”
Section: Introductionmentioning
confidence: 99%
“…PH, psyllium husk; PVA, polyvinyl alcohol them more stable toward structural changes due to temperature and pH shifts, than other existing lipid and protein-based biopolymers. 68 The structural similarity of plant-based polysaccharides to glycosaminoglycans (GAGs), that form a part of the protein found in the connective tissue and ECM of many cell types, renders them more biocompatible than contemporary biopolymers. 69 Although, PVA has now been used in many biomedical applications for over half a century, a plant-based natural polysaccharide always gets an upper hand in comparison to a synthetic polymer.…”
Section: Discussionmentioning
confidence: 99%
“…PH‐based nanofibers exhibit multiple advantages over PVA and PVA/G nanofibers. Apart from its biodegradable nature, easy availability, low toxicity, nonantigenicity, low cost, better biocompatibility in comparison to synthetic polymers; psyllium polysaccharides are bound by strong glycosidic bonds that make them more stable toward structural changes due to temperature and pH shifts, than other existing lipid and protein‐based biopolymers 68 . The structural similarity of plant‐based polysaccharides to glycosaminoglycans (GAGs), that form a part of the protein found in the connective tissue and ECM of many cell types, renders them more biocompatible than contemporary biopolymers 69 .…”
Section: Discussionmentioning
confidence: 99%